Combination therapy of infantile hemangiomas with pulsed dye laser and Nd:YAG laser is effective and safe. (14th May 2014) - Kaune, Kjell M.; Lauerer, Peter; Kietz, Silke; Eich, Christoph; Thoms, Kai‐Martin; Schön, Michael P.; Zutt, Markus
Summary Background Infantile hemangiomas (IH) can cause severe complications such as obstruction, ulceration or heart failure. Therefore, in certain difficult‐to‐treat areas, or when there is no sign of involution, early and effective therapy is required. In rare instances, systemic treatments, like the beta‐blocker propranolol and oral corticosteroids, can cause serious side effects. Effective and well‐tolerated local treatment options are thus desirable as additive or alternative methods. Patients and Methods In this retrospective interdisciplinary study, 38 children with 77 IH were treated with pulsed dye laser (PDL) (595 nm) and Nd:YAG laser (1, 064 nm). The treatment success and side effects were evaluated according to objective and subjective parameters, including hemangioma thickness measured by ultrasound and the parents' evaluation of treatment. Results All 77 treated IH responded to the therapy, of which 52.8 % healed after the end of treatment and 47.2 % had only minimum residual components. The success of treatment was assessed by the parents in 92.6 % as very good or good. Transient blistering occurred as the main side effect in 45.9 %. Conclusions Combination therapy with PDL and Nd:YAG laser represents an effective local method for IH with minimal side effects.